Hypoxic colorectal cancer‐derived extracellular vesicles deliver microRNA‐361‐3p to facilitate cell proliferation by targeting TRAF3 via the noncanonical NF‐κB pathways. Issue 3 (17th March 2021) - Li, Jie; Yang, Peng; Chen, Fangyu; Tan, Yuqian; Huang, Changzhi; Shen, Hengyang; Peng, Chaofan; Feng, Yifei; Sun, Yueming
Abstract: Background: Hypoxic tumour microenvironment (TME) is a key regulator in cancer progression. However, the communications between hypoxic cells and other components in TME during colorectal cancer (CRC) progression via extracellular vesicles (EVs) remain unclear. Methods: High‐throughput sequencing was employed to detect aberrantly expressed microRNAs (miRNAs) in hypoxic EVs. Quantitative real‐time PCR was used to confirm and screen preliminarily candidate miRNAs. The effects of EVs derived from hypoxia (<1% O2 ) and miR‐361‐3p on CRC growth were assessed using CCK‐8 assays, colony formation assays, EdU assays, flow cytometric assays and mouse xenograft. Then, the specific mechanisms of miR‐361‐3p were investigated by RNA immunoprecipitation, luciferase reporter assay, Western blot, chromatin immunoprecipitation, immunohistochemistry and rescue experiments. Results: The level of miR‐361‐3p expression was remarkably elevated in hypoxic EVs and can be transferred to CRC cells. Functional experiments exhibited that hypoxic EVs facilitated cell growth and suppressed cell apoptosis by transferring miR‐361‐3p of CRC. Hypoxia‐inducible factor‐1α induced the elevation of miR‐361‐3p levels in hypoxic EVs. Upregulated miR‐361‐3p in CRC inhibited cell apoptosis and facilitated cell growth by directly targeting TNF receptor‐associated factor 3, which consequently activated the noncanonical NF‐κB pathway. Moreover, the high expression of circulating exosomal miR‐361‐3p was correlated to worse prognosis of CRC patients. Conclusions: Altogether, the abnormality of exosomal miR‐361‐3p derived from hypoxia acts vital roles in the regulation of CRC growth and apoptosis and can be an emerging prognostic biomarker and a therapeutic target for CRC patients. Abstract : Hypoxic colorectal cancer‐derived extracellular vesicles deliver microRNA‐361‐3p to facilitate cell proliferation by targeting TRAF3 via the noncanonical NF‐κB pathways. Hypoxia‐inducible factor‐1α induced the elevation of miR‐361‐3p levels in hypoxic EVs. Moreover, the high level of exosomal miR‐361‐3p in the serum from CRC patients was correlated to poor prognosis.